2007
DOI: 10.1093/rfs/hhm066
|View full text |Cite
|
Sign up to set email alerts
|

Where Is the Market? Evidence from Cross-Listings in the United States

Abstract: We analyze the location of stock trading for firms with a US cross-listing. The fraction of trading that occurs in the United States tends to be larger for companies from countries that are geographically close to the United States and feature low financial development and poor insider trading protection. For companies based in developed countries, trading volume in the United States is larger if the company is small, volatile, and technology-oriented, while this does not apply to emerging country firms. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 54 publications
11
65
1
1
Order By: Relevance
“…In line with the findings of Halling et al (2008), the size of a company (TA), measured by its total assets, is significantly positively related to the fraction of foreign to local liquidity. An increase in total assets by one standard deviation from the mean leads to an increase in the liquidity ratio of 14.6%.…”
Section: Control Variablessupporting
confidence: 74%
See 1 more Smart Citation
“…In line with the findings of Halling et al (2008), the size of a company (TA), measured by its total assets, is significantly positively related to the fraction of foreign to local liquidity. An increase in total assets by one standard deviation from the mean leads to an increase in the liquidity ratio of 14.6%.…”
Section: Control Variablessupporting
confidence: 74%
“…Focusing on the location of local trading of stocks dually-listed in the U.S., Halling, et al (2008) identified a variety of variables influencing the distribution of trading volume.…”
Section: Hypothesis H42: An Improvement In the Regulatory Environmenmentioning
confidence: 99%
“…Traders who have to pay both prices are assumed to expect the exchange in which the security is listed as being the more liquid one, hence, increasing the utility of traders trading on this platform by k. This is in line with the empirical observation that the liquidity of a stock is usually concentrated on the stock exchange where the company got its primary listing (see Halling, Pagano, Randl, and Zechner (2008)). In the following, we refer to k as the liquidity parameter.…”
Section: The Basic Modelmentioning
confidence: 56%
“…First, some Chinese firms are less motived to obtain better stock performance on foreign exchanges but are more interested in potential benefits such as more convenient mergers and acquisitions or simply greater product market visibility and reputation (Halling et al 2007). …”
Section: Discussionmentioning
confidence: 99%